An estimate concerning the difference between minimizer and boundary value in some polyconvex problems. (February 2022) - Colucci, Renato; Leonetti, Francesco; Treu, Giulia
Abstract: This paper is concerned with regularity of minimizers of integral functionals with polyconvex potentials. In particular we obtain bounds on the difference | u − u ∗ | ∞ for minimizers u : Ω ⊂ R 3 → R 3 of problem min ∫ Ω f ( x, D v ( x ) ) d x, v ∈ u ∗ + W 0 1, p ( Ω, R 3 ) .